Tea plantations in crisis : an overview - Manikam, P. P.; Social Scientists Association of Sri Lanka (Colombo : Social Scientists' Association, 1995)
With special reference to Sri Lanka.
Keywords: Tea trade -- Sri Lanka; C-21